Lagrangian Coherent Structures in the Mediterranean Sea: Seasonality and basin regimes - Antivachis, Dimitrios; Vervatis, Vassilios; Sofianos, Sarantis (2023)
The dynamics of fluid flows give rise to robust, persistent circulation features that underpin the flow and exert strong control over the advection of water masses, either enhancing it or suppressing it, collectively known as lagrangian coherent structures. Lagrangian approaches and metrics have been shown to be better suited than eulerian ones at locating and delineating such structures and capturing the effect they have on the formation and dispersion of water masses, particularly at the smaller scales. In this paper, we use the framework of lagrangian coherent structures to analyse the ocean velocity fields over a climatological year obtained from a high-resolution eddy-resolving model in order to investigate the lagrangian regimes that affect the motion, separation and mixing of water masses in the Mediterranean Sea. The lagrangian regimes that develop in each sub-basin over the course of the year are characterised and regions of persistent lagrangian activity and coherent structure formation and presence are identified. A quantitative picture of the seasonal variability of the lagrangian coherent structure-induced horizontal mixing and vortex formation is obtained.
Keywords: Horizontal mixing; Lagrangian Coherent Structures; Mediterranean Sea; Seasonal variability